Comparison of neutron activation analysis (NAA) and energy dispersive X-ray fluorescence (XRF) spectrometry for the non-destructive analysis of coins minted under the early Piast dynasty - Bolewski, Andrzej; Matosz, Marta; Pohorecki, Władysław; del Hoyo-Meléndez, Julio M. (Radiation physics and chemistry (Oxford, England : 1993), 2020)
Surface enrichment of silver-copper alloys is a current subject of research in archaeometry, while its origin in cultural heritage objects remains unclear. Due to their low penetration depth, surface techniques may give misleading results if the objects analyzed show this enrichment behavior. To study this effect, the surface and bulk composition of a group of Polish coins minted in the X-XI centuries during the early Piast dynasty were investigated using energy dispersive X-ray fluorescence (XRF) spectrometry and neutron activation analysis (NAA). A comparison of the results obtained using these two techniques permitted to classify the coins in two groups. The first group exhibited similar bulk and surface compositions, while coins in the second one showed silver surface enrichment. In addition, a correlation between silver and gold was observed after evaluating the analytical results providing a first step in the determination of silver provenance. •Polish coins of the early Piast dynasty from the X-XI centuries were investigated.•Quantitative XRF and NAA methods were compared.•The main alloying elements were Ag and Cu; with Ag concentrations in the 82–98% range.•Different coin compositions at the surface and in the bulk were examined.